High Mobility Group Box Protein 1 Serves as a Potential Prognostic Marker of Lung Cancer and Promotes Its Invasion and Metastasis by Matrix Metalloproteinase-2 in a Nuclear Factor-κB-Dependent Manner. (19th April 2018) - Wu, Xiaojin; Wang, Weitao; Chen, Yuanyuan; Liu, Xiangqun; Wang, Jindong; Qin, Xiaobin; Yuan, Dawei; Yu, Tao; Chen, Guangxia; Mi, Yanyan; Mou, Jie; Cui, Jinpeng; et al.
Abstract : Several studies have reported a significant role of high mobility group box protein 1 (HMGB1) in lung cancer. Nevertheless, there is a lack of knowledge regarding the expression of HMGB1 and its correlation with the clinicopathological features of lung cancer. In addition, the potential molecular mechanisms underlying the role of HMGB1 in lung cancer are still unknown. We therefore investigated the clinicopathological and prognostic significance as well as the potential role of HMGB1 in the development and progression of lung cancer. HMGB1 expression in the tumor tissues of the cohort correlated with clinicopathological features. Moreover, lung cell migration and invasion were significantly increased after treatment with HMGB1. The matrix metalloproteinase-2 (MMP-2) expression and activity were upregulated after treatment with HMGB1, while the upregulated expression of MMP-2 stimulated by HMGB1 in lung cancer cells was significantly reduced with the blockage of si-p65. These results indicated that HMGB1 expression was significantly associated with lung cancer progression. We also showed that HMGB1 promoted lung cancer invasion and metastasis by upregulating the expression and activity of MMP-2 in an NF- κ B-dependent manner. Taken together, these data suggested that HMGB1 may be a potential prognosis and therapeutic marker for lung cancer.